A season of voting : the Japanese elections of 1976 and 1977 - Passin, Herbert (Washington : American Enterprise Institute for Public Policy Research, 1979)
The book analyzes Japan's last two elections, the 1976 house of Representatives election and the 1977 House of Councillors election.
Includes bibliographical references and index.
aia 14/05/2018
Loans.
Keywords: Elections; Voting; Politics and government; Japan